Selenium supplementation in radiotherapy patients: do we need to measure selenium levels in serum or blood regularly prior radiotherapy? - Muecke, Ralph (Radiat Oncol, 2014)
Considering the review by Puspitasari and colleagues, an additional discussion of the endpoints of the Se supplementation studies described would be helpful. In our view, selenium can safely be given to selenium-deficient cancer patients prior to and during radiotherapy. Therefore, in order to help the radiation oncologist in decision making, we strongly advocate to determine the selenium status prior to and during a potential adjuvant selenium supplementation, e.g. when trying to ease the side-effects of radiation treatment or in the aftercare situation when the selenium status may become insufficient.